The clinical effectiveness of staple line reinforcement with different matrix used in surgery - Jing, Wei; Huang, Yiqian; Feng, Jin; Li, Hongyang; Yu, Xueqiao; Zhao, Bo; Wei, Pengfei (Frontiers in Bioengineering and Biotechnology, 2023)
Stapler has been widely used in clinic, however the challenge associated with complications, such as bleeding and leakage, is still a concern for surgeons. Reinforcement of the staple line with buttress materials is recommended to help solve the problems. This review systematically summarizes the characteristics and applications of the buttress materials. Firstly, the physical and chemical properties of the synthetic polymer materials and extracellular matrix used for the buttress materials have been introduced, as well as their advantages and disadvantages in clinical application. Secondly, we reviewed the clinical effects of the reinforcement mesh in pneumonectomy, sleeve gastrectomy, pancreatectomy and colorectal resection. Through the analysis of a large number of research data, we believe that buttress materials play an important role in improving the staple line strength and reduce the probability of complications such as bleeding and leakage. However, considering the requirements of bioactivity, degradability and biosafety, the buttress material made of non-crosslinked SIS (submucosa of small intestine) matrix material is the preferred candidate, which has high research and application value, but more research is needed to confirm this. This review aims to provide comprehensive guidance on the selection of the materials for staple line reinforcement.